Cadmium (Cd) and Lead (Pb) Induced Changes in Growth, Some Biochemical Attributes, and Mineral Accumulation in Two Cultivars of Mung Bean [Vigna radiata (L.) Wilczek]. Issue 4 (21st February 2016) - Ashraf, M. Yasin; Roohi, Mahnaz; Iqbal, Zafar; Ashraf, M.; Öztürk, Münir; Gücel, Salih
ABSTRACT: Addition of cadmium, lead, and cadmium + lead (Cd, Pb, and Cd+Pb) to growth medium leads to a reduction in seed germination, length, fresh and dry biomass of shoots and roots, total chlorophyll, chlorophyll a, chlorophyll b, and soluble proteins in plants. This study was undertaken on two mungbean cultivars (MN-92 and MN-98). Application of these metals in the growth medium reduced the bioabsorption of calcium (Ca), magnesium (Mg), and potassium (K). Concentrations of all the metals were greater in the roots than in the shoots except for K, which was greater in the shoots. Mungbean cultivar NM-98 performed better than NM-92 in response to heavy-metal toxicity. Overall, the metal-induced physiobiochemical changes resulted in reduced growth of both mungbean cultivars.